ONE-YEAR INCIDENCE OF CORONARY EVENTS IN MYOCARDIAL INFARCTION PATIENTS AFTER SUCCESSFUL THROMBOLYSIS AND POSTPONED PERCUTANEOUS CORONARY INTERVENTION - A. Yu. Lebedeva; S. A. Davtyan; L. L. Klykov; M. A. Kudinova; V. V. Krylov (Российский кардиологический журнал)
.